Comparing the preclinical risk profile of inhalable candidate and potential candidate modified risk tobacco products: A bridging use case. (2020) - Schlage, Walter K.; Titz, Bjoern; Iskandar, Anita; Poussin, Carine; Van der Toorn, Marco; Wong, Ee Tsin; Pratte, Pascal; Maeder, Serge; Schaller, Jean-Pierre; Pospisil, Pavel; Boue, Stephanie; Vuillaume, Grégory; et al.
Graphical abstract: Highlights: Heated tobacco products tested for reduced exposure and reduced risk properties. Bridging opportunities for nonclinical results from two heated tobacco products. Similarly reduced impact on apical and molecular endpoints relative to cigarettes. Evidence evaluated along a "causal chain of events leading to disease" (CELSD). Representative assays along CELSD could support nonclinical substantial equivalence. Abstract: Cigarette smoking causes major preventable diseases, morbidity, and mortality worldwide. Smoking cessation and prevention of smoking initiation are the preferred means for reducing these risks. Less harmful tobacco products, termed modified-risk tobacco products (MRTP), are being developed as a potential alternative for current adult smokers who would otherwise continue smoking. According to a regulatory framework issued by the US Food and Drug Administration, a manufacturer must provide comprehensive scientific evidence that the product significantly reduces harm and the risk of tobacco-related diseases, in order to obtain marketing authorization for a new MRTP. For new tobacco products similar to an already approved predicate product, the FDA has foreseen a simplified procedure for assessing "substantial equivalence". In this article, we present a use case that bridges the nonclinical evidence from previous studies demonstrating the relatively reduced harm potential of two heat-not-burn products based on different tobacco heating principles. The nonclinical evidence was collected along a "causal chain of events leading to disease" (CELSD) to systematically follow the consequences of reduced exposure to toxicants (relative to cigarette smoke) through increasing levels of biological complexity up to disease manifestation in animal models of human disease. This approach leverages the principles of systems biology and toxicology as a basis for further extrapolation to human studies. The experimental results demonstrate a similarly reduced impact of both products on apical and molecular endpoints, no novel effects not seen with cigarette smoke exposure, and an effect of switching from cigarettes to either MRTP that is comparable to that of complete smoking cessation. Ideally, a subset of representative assays from the presented sequence along the CELSD could be sufficient for predicting similarity or substantial equivalence in the nonclinical impact of novel products; this would require further validation, for which the present use case could serve as a starting point.